DNMT1 constrains IFNβ-mediated anti-tumor immunity and PD-L1 expression to reduce the efficacy of radiotherapy and immunotherapy. (1st January 2021) - Huang, Kevin Chih-Yang; Chiang, Shu-Fen; Ke, Tao-Wei; Chen, Tsung-Wei; Hu, Ching-Han; Yang, Pei-Chen; Chang, Hsin-Yu; Liang, Ji-An; Chen, William Tzu-Liang; Chao, K. S. Clifford
ABSTRACT: Radiotherapy can boost the therapeutic response to immune checkpoint inhibitors (ICIs) by recruiting T lymphocytes and upregulating PD-L1 expression within the tumor microenvironment (TME). However, in some cases, tumor PD-L1 expression cannot be induced, even in the presence of abundant T lymphocytes, in locally advanced colorectal cancer patients who receive preoperative neoadjuvant concurrent chemoradiotherapy (CCRT). In this study, we found that PD-L1 promoter methylation is negatively correlated with tumor PD-L1 expression and is an independent biomarker for locally advanced colorectal cancer patients. PD-L1 methylation ( mCD274 ) was significantly associated with shorter disease-free survival (cg15837913 loci, p = .0124). By multivariate Cox proportional hazards analyses including influent factors, mCD274 was classified as an independent prognostic factor for poor 5-year DFS [cg15837913, hazard ratio: HR = 4.06, 95% CI = 1.407–11.716, p = .01]. We found that the immunomodulatory agent DNA methyltransferase inhibitor (DNMTi) led to demethylation of the PD-L1 promoter and increased radiotherapy-induced PD-L1 upregulation via interferon β (IFNβ). DNMTi not only induced tumor PD-L1 expression but increased the expression of immune-related genes as well as intratumoral T cell infiltration in vivo . Furthermore, DNMTi strongly enhanced the response to combined treatment with radiotherapy and anti-PD-L1 inhibitors, and prolonged survival in microsatellite stability (MSS) colorectal model. Therefore, DNMTi remodeled the tumor microenvironment to improve the effect of radiotherapy and anti-PD-L1 immunotherapy by directly triggering tumor PD-L1 expression and eliciting stronger immune responses, which may provide potential clinical benefits to colorectal cancer patients in the future.